PERBANDINGAN INDEKS KARIES ANTARA ANAK YANG MENGKONSUMSI SUSU BOTOL DENGAN TANPA BOTOL USIA 2-5 TAHUN Tinjauan Playgroup Islam Terpadu Ukhuwah Banjarmasin - Ghaitsa, Ghaitsa; widodo, widodo; Adhani, Rosihan (FKG Unlam, 2017)
Background: The prevalence of bottle caries in Indonesia is quite high at 48% is due to the high percentage of children drinking milk bottles which given while sleeping. Consuming milk formula using a bottle can cause caries, because the product of milk contain carbohydrates. Carbohydrate which contact with teeth will be fermented by bacteria become acid. This situation will cause the demineralization process that dissolves the enamel structure. Caries which caused by bottle feeding is known as Nursing Mouth Caries (NMC). Purpose: The purpose of this research is to know the difference of caries index of deciduous teeth between children who consumed milk with and without bottle.Methods: The target of this research is the students of Playgroup Islam Terpadu Ukhuwah Banjarmasin age 2-5 years with total sample of 80 children who were divided in to two groups, 40 children consumed milk with bottle and 40 children consumed milk without bottle. This research uses cross sectional design. def-t index is used as the measuring tool for deciduous teeth with caries.Results: The results showed that the index of caries in children who consumed milk with bottle is 5,3 which included in the high category, while the index of caries in children who consumed milk without bottle is 3,4 which included in the medium category. Statictical analysis of the results obtained value of p = 0,032 (p < 0,05) which indicated significant difference between the index of caries children who consumed milk with and without bottle. Children who consumed milk using bottle causing pool and contact with teeth. This situation will lower the pH of mouth and self cleansing diminished so that the process of demineralization happened. Conclusion: The conclusion is caries index in children who consumed milk with using bottle is higher than without using bottle.